KEBERADAAN GAMELAN BATEL DI ERA GLOBALISASI - I Nyoman Surianta (UNHI PRESS, 2021)
Today's art, in terms of quantity, has grown tremendously. However, this tremendous development was not followed by several other arts. On the one hand, there are those that are experiencing tremendous development, on the other hand, there are arts that are experiencing marginalization, which is caused by the lack of attention to these arts. Gamelan Batel is one of the arts that has become an art that is experiencing a shift. The existence of this art is very concerning, where the cause of the shift is the arts that grow and develop in society. The shift in the art of batel is caused by the performers of the arts themselves, one of which is the dalang. The puppeteers in the current era of globalization prefer other gamelan to join and as an accompaniment in wayang performances. The marginalization of the Batel Gamelan in Sibanggede Village can be seen by the decline in the values ​​of traditional arts in the community, the displacement of traditional arts, the secularization of traditional arts, the narrowing of the space for performing traditional arts.